Therapeutic Antibodies for the Treatment of Pancreatic Cancer. (2010) - Chames, Patrick; Kerfelec, Brigitte; Baty, Daniel
Abstract : Pancreatic cancer is a devastating disease with the worst mortality rate and an overall 5-year survival rate lower than 5%. In the U.S., this disease is the fourth leading cause of death and represents 6% of all cancer-related deaths. Gemcitabine, the current standard first-line treatment, offers marginal benefits to patients in terms of symptom control and prolongation of life. Since 1996, about 20 randomized phase III trials have been performed to improve the efficacy of gemcitabine, with little success regarding a significant improvement in survival outcomes. The need for novel therapeutic strategies, such as target therapy, is obvious. Monoclonal antibodies have finally come of age as therapeutics and several molecules are now approved for cancer therapies. This review aims to give a general view on the clinical results obtained so far by antibodies for the treatment of pancreatic cancer and describes the most promising avenues toward a significant improvement in the treatment of this frustrating disease.